Maringá and its historical heritage: a case study on the cathedral of the Assumption - doi: 10.4025/actascitechnol.v35i4.11063 - Barbosa, Leonardo Cassimiro; Barbosa, Priscila Pasti; Jung, Norma Eliane; De Angelis, Bruno Luiz Domingos; De Angelis Neto, Generoso (Acta Scientiarum. Technology, 2013)
The most tangible register of a civilization´s evolution is the heritage it preserves over the years. It is a vehicle for the transmission of peoples´ memory and culture. Although the city of Maringa in the state of Paraná, Brazil, is just 66 years old, it has several important buildings within its urban context whose preservation is not guaranteed by law. In fact, they are in danger of disappearing amid the city´s fast growth. Current research, surveying the preservation state of historical buildings in the municipality, is based on published studies, research at the City Hall, reports by the Historical Heritage Commission and in loco visits, with special emphasis on the Cathedral of the Assumption, the city´s symbol, whose preservation is still not legally guaranteed. The history of the building of the Cathedral, its most relevant external and internal architectonic features and its furniture for future inventories are focused. Current study raised the historic deployment of the Cathedral, its most relevant architectural features, both exterior and interior, including some of its details, to serve as a basis for inventories for future legal registrations and interventions. Â